Sowing depth and seed specific weights on emergence of the weed Urochloa ruziziensis on field conditions - Marques, Ricardo Fagundes [UNESP]; Gomes, Francielly Rodrigues [UNESP]; Martins, Cibele Chalita [UNESP]; de Marchi, Sidnei Roberto; Martins, Dagoberto [UNESP] (Revista Brasileira de Ciencias Agrarias, 2024)
The objective of this study was to evaluate the effects of sowing depths and specific seed weights on the emergence of Urochloa ruziziensis in the field. A randomized block experimental design was adopted, with four replications and the treatments distributed in a 6 × 3 factorial scheme, with six sowing depths (1.0, 2.0, 4.0, 8.0, 12.0, and 16.0 cm) associated with three specific seed weights (low, medium, and high). The effects of the treatments were evaluated using seedling emergence tests in the field. The different specific seed weights did not reduce the emergence of U. ruziziensis seedlings in the field. The seedlings of the weed U. ruziziensis emerged at depths of up to 12 cm. Sowings between 1.0 and 4.0 cm deep gave the highest values for the percentage and speed of emergence and the shortest average time for U. ruziziensis seedlings to emerge in the field. The relative frequency polygons show that depths greater than 2.0 cm slow down the propagation of U. ruziziensis, regardless of the specific weight of the seeds.
Profundidade de semeadura e peso específico das sementes na emergência da planta daninha Urochloa ruziziensis em campo
Keywords: germination; seed physiological quality; specific mass; vertical arrangement; weeds